(3cJGH GdYHGOdIs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3cGJH GdCeQ GdeQHhW s)
(3ChdgG (B:s
(3GdMeO ddg HMeO GdMeO aEfg Chai hdg GdebGe GdCNdU gPG cJGH PcQfG ajg eG fWbJ Hg CdSfI GdYHGOdI YfO JMbjbge HeG Mbbge Hg GdMb ai SQGFQge heGJQLeJg dbdhH GdYGQajf s
(3BNQgG (B:s
(3WdYJ GdTeS bGdhG YJO eLjF RjO acd hGMO efgeG hbJ dUGMHg Je GdcJGH hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1437s
Keywords: (3GdJUha hGdBOGH GdTQYjIs